Ball size and weight effects on throwing kinematics and kinetics in youth baseball athletes - Arnold, C. J.; Hosmer, N.; Moore, M.; Bullock, G.; Nicholson, K. (ISBS Proceedings Archive (Michigan), 2023)
In baseball, youth players play on smaller fields with shorter base path distance, pitching distance, and smaller mounds. Despite this, the baseball itself remains unchanged for youth athletes. This prospective cohort analyzed the kinematics and kinetics of 38 youth baseball pitchers while using modified sized and weighted baseballs. An ANOVA was used to determine statistical significance amongst ball modifications. ANOVA results show significance between the 3oz-5oz baseball with the 3oz baseball decreasing elbow varus torque. This is a preliminary study on the effects of modified baseballs on youth athletes.